O movimento de espiritualidade conjugal das Equipes de Nossa Senhora - ENS: (metodologia, fundamentos bíblico-teológicos e pertinência para a atualidade). - Silva, Sonival Marinho da (2022)
The study major goal study is the Movimento das Equipes de Nossa Senhora (ENS). Marital Spirituality of Our Lady Team Work Affair. (OLTWA). From the fallowing spiritual line of thinking that has been elaborated for more than eight two years, Catholic couples from five continents have been using the method developed by Priest (Father) Padre Henri Caffarel, ENS apply it to this movement and contribute to its development. Since 1939, young couples from Juventude Operária Cristã e da Ação Católica, have been looking for Father Caffarel, with the spiritual desire that could specifically correspond to their married status. Once it was not something that hasn´t been previewed and established, a challenging point has been set up through priest´s answers: “let´s do it together!”, by giving rise to the couple spirituality movement. This research has is focus on the constitutive elements of this spirituality at ENS. For this reason, it is a bibliographic research based on documents of the movement, church documents and through church documents and from the church context as to Vatican II. In order to analyze the steps taken by this movement the research was divided into three steps: 1) Matters regarding to historic context and social events that provide methodological management applied in the couple movement frame; 2) as a second matter, analyze the Theological Biblical Bases of ENS, its specialties, limits; and finality. 3) Matters referring to the search for couple relationship meaning; testifying and faith in their daily matrimonial life and as a final closing, the specific contribution of lay people the ENS in the church mission. The whole research has as a major goal to valorize and point out the unique richness of ENS as to the formation of catholic couples as to the church mission.